PENERAPAN STRATEGI MTMA (MEET TUGAS MEET APRESIASI) UNTUK MENINGKATKAN HASIL BELAJAR IPS PESERTA DIDIK KELAS VII-F SMPN 3 CILEGON DI MASA PANDEMI COVID-19 - Yosie Kristin Pandriyani (Universitas Sultan Ageng Tirtayasa, 2022)
The Covid-19 pandemic makes face-to-face learning switching to network-based (online), various platforms are used by teachers and obliging students to take advantage of information technology to support learning. The MTMA learning strategy (Meeting, Assignment, Meeting, Appreciation) is a one of from innovation in online learning using utilizing Microsoft 365. The aim is to determine the effectiveness of implementing the MTMA strategy in improving IPS learning result of student. This research uses Classroom Action Research conducted in two cycles. Implementation in The Acamdemic yeara 2020/2021, from March 2021 to April 2021 for class VII-F students of SMPN 3 Cilegon. The required data, obtained from knowledge assessment from written tests, assignments, and from skills assessments in the from of practical assessments, product assessments, and attitude assessments.The success criteria determined based on 2 things, there is; KKM and Achievement, achieved. the research results show; 1) all students (100%) have reached> KKM (65) in the assessment of knowledge and skills, and have a good predicate on the assessment of attitudes; and 2) all students (100%) have achieved ≥ achievement (76) in the knowledge assessment, for the assessment of skills all students (100%) have reached ≥ achievement (76) in the practical assessment and 65.52% have reached ≥ achievement (76) on product assessment, and has a good predicate on attitude assessment.